2018
DOI: 10.1038/gim.2017.165
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SLC20A1 and SLC15A4 among other genes as potential risk factors for combined pituitary hormone deficiency

Abstract: Purpose: Combined pituitary hormone deficiency (CPHD) is characterized by a malformed or underdeveloped pituitary gland resulting in an impaired pituitary hormone secretion. Several transcription factors have been described in its etiology, but defects in known genes account for only a small proportion of cases.Methods: To identify novel genetic causes for congenital hypopituitarism, we performed exome-sequencing studies on 10 patients with CPHD and their unaffected parents. Two candidate genes were sequenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…As previously proposed by Reis et al (), we hypothesize that the frequently reported phenotypic variability and incomplete penetrance of BMP4 mutations, may be explained by the aggregate interaction/contribution of additional genetic variants or predisposing factors, inherited according to an oligogenic pattern, as recently suggested for other clinical presentations of congenital hypopituitarism by three independent groups who approached the genetic analysis of a limited number of patients with specific forms of congenital hypopituitarism by whole exome sequencing (Guo et al, ; Simm et al, ; Zwaveling‐Soonawala et al, ). While only the article by Zwaveling‐Soonawala et al, (2017) reported the identification of a novel in‐frame BPM4 deletion in one of the examined patients, all three studies suggested a polygenic etiology in a significant proportion of the examined patients (83, 65, and 30%, respectively).…”
Section: Discussionmentioning
confidence: 56%
“…As previously proposed by Reis et al (), we hypothesize that the frequently reported phenotypic variability and incomplete penetrance of BMP4 mutations, may be explained by the aggregate interaction/contribution of additional genetic variants or predisposing factors, inherited according to an oligogenic pattern, as recently suggested for other clinical presentations of congenital hypopituitarism by three independent groups who approached the genetic analysis of a limited number of patients with specific forms of congenital hypopituitarism by whole exome sequencing (Guo et al, ; Simm et al, ; Zwaveling‐Soonawala et al, ). While only the article by Zwaveling‐Soonawala et al, (2017) reported the identification of a novel in‐frame BPM4 deletion in one of the examined patients, all three studies suggested a polygenic etiology in a significant proportion of the examined patients (83, 65, and 30%, respectively).…”
Section: Discussionmentioning
confidence: 56%
“…Additionally, few patients have been screened for mutations in all the genes by using targeted sequencing panels. It is important to note that between 80-90% of CH (5). The cost and speed of NGS is decreasing rapidly, enabling a higher volume of patients to benefit from its resources, however at present the number is limited to only a select few unique cases where no clear causative genes are suspected, or to familial cases or those born to consanguineous unions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that, as is the case with Kallmann syndrome/Hypogonadotrophic hypogonadism, oligogenicity may contribute to the complex and highly variable phenotypes and penetrance observed in CH patients. Rare and unique forms of CH with accompanying midline abnormalities may be caused by mutations in two or more genes involved in the complex signaling pathways that are critical for HP embryonic development (5). The limited number of patients reported in cohort studies, the variable frequency of mutations in different ethnic backgrounds, and the marked phenotypic variability associated with different genes, all make genotypephenotype correlations difficult to establish (6).…”
mentioning
confidence: 99%
“…All variants in genes present in the cDNA libraries were confirmed by Sanger sequencing as described previously [15]. For sequencing the coding region of TRPC4AP, PCR products of exonic amplicons were generated using Paq5000 Polymerase (Agilent, Santa Clara, CA, USA) and subsequently sequenced (GATC, Konstanz, Germany).…”
Section: Sanger Sequencingmentioning
confidence: 99%